New Mitochondrial Genomes of Ithonidae (Neuroptera) and Higher Phylogenetic Implications - Ruyue Zhang; Yunlan Jiang; Mina Zhong; Shutong Wang; Yuyu Wang (Insects)
Ithonidae (moth lacewings) are an enigmatic, small family of the insect order Neuroptera (lacewings). Its phylogenetic position within Neuroptera and internal subfamily relationships remain unresolved. In this study, the complete mitochondrial genome (mitogenome) of Ithone fulva Tillyard, 1916 representing the first mitogenome of Ithoninae, as well as the complete mitogenome of Rapisma gaoligongensis Liu, Li and Yang, 2018, were newly reported. Molecular phylogenetic trees recovered Ithonidae as the sister group to Chrysopidae + Hemerobiidae. Ithoninae was demonstrated to be the sister group to Polystoechotinae + Rapismatinae across all topologies. Divergence time estimation revealed that Ithonidae originated during the Mid-Triassic. Ithoninae diverged from Polystoechotinae and Rapismatinae in the Late Triassic, while Polystoechotinae diverged from Rapismatinae in the Middle Jurassic. Moreover, more comprehensive samplings, as well as whole genome data, are needed to reconstruct a comprehensive framework of the phylogeny of Ithonidae, as well as Neuropteida.